Forensic psychiatric patients’ experiences of participating in administrative court proceedings concerning the continuation of forensic psychiatric care - Söderberg, Andreas; Wallinius, Märta; Munthe, Christian; Rask, Mikael; Hörberg, Ulrica (Frontiers in Psychiatry, 2023)
Introduction Previous studies show that both staff and patients describe patient participation as a challenge in forensic psychiatry. One reason may be that the forensic psychiatric process is difficult to understand and is experienced as being slow and complex. The proceedings in an administrative court are a core element in forensic psychiatric care as it constitutes the legal authority that legitimizes the deprivation of liberty. A better understanding about how patients experience these proceedings can contribute with important knowledge about how forensic psychiatric care can be understood from a patient perspective. The aim of the study was to describe patients’ lived experiences of participating in oral hearings in an administrative court concerning the continuation of their forensic psychiatric care. Materials and methods This is a phenomenological study performed in a Swedish context with a total of 20 interviews conducted with a Reflective Lifeworld Research (RLR) approach. Results The results reveal three themes; A significant, correct but meaningless formality; An imbalance of power within the hearings; and Existential and practical disorientation. Conclusion The findings show how these court proceedings concerning the continuation of forensic psychiatric care are often experienced as challenging. This is partly due to the care structure in forensic psychiatry and that the purpose of the hearings is difficult to comprehend and is perceived as unjust by patients. Another challenge is of a more existential dimension, where the main character in a hearing is most likely in a situation that would be stressful for anyone. However, the focus on danger can make this experience even more intense. An increased transparency on this legal process along with more discussion and education for both patients and staff is called for based on the results.